Incorporating water production and carbon sequestration into forest management planning: a case study in Yalnızçcam planning unit - Baskent, E. Z.; Mumcu Küçüker, D. (Forest Systems, 2010)
Sustainable forest management requires smart integration of forest values both to control forest ecosystems and to satisfy the needs and expectations of stakeholders. This research initiative aimed to integrate water and carbon values into forest management plan and explain their effects on forest dynamics. Alternative management strategies with a mix of management objectives maximizing the amount or NPV (Net Present Value) of timber, carbon and water production along with constraints such as area, volume control and ending inventory were developed. A linear programming (LP) model with a planning horizon of 100 years and periods of 10 years was developed. Model outputs as NPV and amounts of timber, water and carbon were used as performance indicators to discuss forest dynamics under various management strategies. The results showed that water NPV aimed strategies (*W) provided minimum timber production and maximum water production. Besides, even though timber NPV aimed strategies (*T) obtained maximum NPV of timber as expected, surprisingly maximum timber and carbon production were provided by carbon NPV aimed strategies (*C) due mainly to afforestation of large forest openings in the case study area. The results indicated that the performance of a management strategy depends highly on the contents of a strategy and the initial forest structure aside from the growth rate.